The STOKAYS Application Design For Inventory Recording And Control Based On Appsheet Utilizes Min-Max And FEFO At FB Stores - Vinisya Nur Kusuma Dewi; Amay Suherman; Saskia Kanisaa Puspanikan (Journal Industrial Engineering and Management (JUST-ME), 2026)
Inventory recording and control play an important role in maintaining smooth warehouse operations, especially for businesses in the food sector that depend on the availability of raw materials. FB Stores is a Micro Small Medium Enterprises (MSMEs) in the field of processing various breads and cakes. During inventory management, FB Stores has not implemented either manual or digital inventory records, which makes it difficult to monitor the amount of raw materials available, excess and shortages, and expired materials. This study aims to design the AppSheet-based STOKAYS application using the waterfall method, which consists of the design, implementation, and testing stages using the black box method. The test results show that the STOKAYS application successfully meets the needs of recording and controlling supplies with min-max and FEFO features in real time. This application is expected to be an effective digital solution for MSMEs in improving inventory management efficiency and reducing the risk of wasting raw materials.